STUDI KELAYAKAN THERMOELECTRIC GENERATOR DARI ALUMUNIUM (Al) DAN KARBON (C) SEBAGAI SOLUSI LAIN ENERGI TERBARUKAN - Aliyu, Asniar (KURVATEK, 2021)
This study aims to create a prototype of a Thermoelectric Generator which is composed of a set of Aluminum (Al) and Carbon (C) series thermocouples as an alternative energy source. The initial stage in this research is to make a thermoelectric generator that is composed of 120 series thermocouple pairs or consists of 6 thermopiles (20 thermocouple pairs) arranged in series. Then the hot side is given a heat source using an electric iron and the cold side is equipped with a cooling fan and measures the output voltage generated based on changes in the heat generated by the electric iron. The test results show that temperatures up to 50Â°C produce a DC output voltage with a low increase in voltage change, while above that temperature the output voltage increases significantly. This shows that based on this initial experiment, Al and C thermoelectric generators are feasible to be used as an alternative energy source.